Conditional deletion of CEACAM1 in hepatic stellate cells causes their activation - Harrison T. Muturi; Hilda E. Ghadieh; Suman Asalla; Sumona G. Lester; Getachew D. Belew; Sobia Zaidi; Raziyeh Abdolahipour; Abhishek P. Shrestha; Agnes O. Portuphy; Hannah L. Stankus; Raghd Abu Helal; Stefaan Verhulst; et al. (Elsevier, 2024)
Objectives: Hepatic CEACAM1 expression declines with advanced hepatic fibrosis stage in patients with metabolic dysfunction-associated steatohepatitis (MASH). Global and hepatocyte-specific deletions of Ceacam1 impair insulin clearance to cause hepatic insulin resistance and steatosis. They also cause hepatic inflammation and fibrosis, a condition characterized by excessive collagen production from activated hepatic stellate cells (HSCs). Given the positive effect of PPARγ on CEACAM1 transcription and on HSCs quiescence, the current studies investigated whether CEACAM1 loss from HSCs causes their activation. Methods: We examined whether lentiviral shRNA-mediated CEACAM1 donwregulation (KD-LX2) activates cultured human LX2 stellate cells. We also generated LratCre + Cc1fl/fl mutants with conditional Ceacam1 deletion in HSCs and characterized their MASH phenotype. Media transfer experiments were employed to examine whether media from mutant human and murine HSCs activate their wild-type counterparts. Results: LratCre + Cc1fl/fl mutants displayed hepatic inflammation and fibrosis but without insulin resistance or hepatic steatosis. Their HSCs, like KD-LX2 cells, underwent myofibroblastic transformation and their media activated wild-type HSCs. This was inhibited by nicotinic acid treatment which blunted the release of IL-6 and fatty acids, both of which activate the epidermal growth factor receptor (EGFR) tyrosine kinase. Gefitinib inhibition of EGFR and its downstream NF-κB/IL-6/STAT3 inflammatory and MAPK-proliferation pathways also blunted HSCs activation in the absence of CEACAM1. Conclusions: Loss of CEACAM1 in HSCs provoked their myofibroblastic transformation in the absence of insulin resistance and hepatic steatosis. This response is mediated by autocrine HSCs activation of the EGFR pathway that amplifies inflammation and proliferation.